Genetic analysis of membrane protein topology by a sandwich gene fusion approach. - Ehrmann, M (1990)
We describe a cloning vector that allows the construction of phoA sandwich fusions in which mature alkaline phosphatase is inserted into target proteins. In contrast to previous fusions obtained using the TnphoA transposon, the entire amino acid sequence of the target protein is present in the fusion product. We have constructed a series of sandwich fusions of alkaline phosphatase to the multispanning cytoplasmic membrane protein MalF. Despite the fact that the alkaline phosphatase was tethered to MalF at both its N and its C terminus, the enzyme exhibited high activity when it was fused to a periplasmic domain of the membrane protein. Cells harboring an alkaline phosphatase sandwich fusion to the end of the first membrane-spanning segment of MalF exhibited both MalF and alkaline phosphatase activity. When alkaline phosphatase was inserted into a cytoplasmic domain of MalF, its specific activity was very low. Our results suggest that the alkaline phosphatase activity of phoA sandwich fusions provides a more sensitive monitor than previous methods of the cellular localization of the domain of the target protein to which the enzyme is fused. Thus, the sandwich fusion approach can give a more accurate picture of membrane protein topology.